Efficacy of a multi-component psychosocial intervention program for caregivers of persons living with neurocognitive disorders, Alexandria, Egypt: A randomized controlled trial - Zeinab Nazeeh Shata (Thieme Medical and Scientific Publishers Pvt. Ltd., 2017)
Background: Unlike other chronic diseases, dementia caregiving is associated with enormous psychological burden, which stresses the need for caregivers-directed psychosocial interventions. Aim: This randomized controlled trial (RCT) was conducted to evaluate the short-term efficacy of a multi-component psychosocial intervention program for informal caregivers of persons with neurocognitive disorders in Alexandria, Egypt. Methods: Informal caregivers (120) were randomly assigned into intervention and control groups. The intervention group (60) participated in a multi-component program of 8 sessions, including psycho-education, group cognitive-behavioral therapy, and group social support. Program primary outcomes were assessed after program termination (post-1), and three months later (post-2). Measured outcomes included caregivers' knowledge, depression and anxiety symptoms, and perceived burden. Results: Caregivers' depression, anxiety, and perceived burden demonstrated significant drop at post-1, and post-2 compared to the control group (P< 0.001). The intervention group showed significant negative absolute change on depression, anxiety, and perceived burden measures, while on the dementia-related knowledge measure, a significant positive absolute change was found at post-1, and post-2 (P< 0.001), in comparison to controls. All outcome measures recorded a large effect size; the highest was for knowledge (partial eta2 = 0.98), and the least was for perceived burden (partial eta2 = 0.71). Conclusion: A multi-component psychosocial intervention for caregivers of persons with neurocognitive disorders demonstrated a short-term efficacy in reducing their burden, depression, and anxiety, as well as improving caregivers' knowledge. However, further research is needed to investigate long-term efficacy of the intervention.